Revising history, constructing the place: the creation of new cultural practices in the Croatian village of Zrin - Lončar, Sanja, etnologinja (Array, 2011)
The paper examines ways in which the revising of history and the construction of places, by focusing on certain historic episodes, influence people's attachment to a place and the creation of new cultural practices.